Intravenous aflibercept in patients with platinum‐resistant, advanced ovarian cancer: Results of a randomized, double‐blind, phase 2, parallel‐arm study. Issue 3 (11th October 2013) - Tew, William P.; Colombo, Nicoletta; Ray‐Coquard, Isabelle; del, Josep M.; Oza, Amit; Pereira, Deolinda; Mammoliti, Serafina; Matei, Daniela; Scambia, Giovanni; Tonkin, Katia; Shun, Zhenming; Sternas, Lars; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND In this randomized phase 2 study, the authors assessed the efficacy and safety of intravenous aflibercept at 2 different doses (2 mg/kg or 4 mg/kg) in patients with recurrent, platinum‐resistant ovarian, peritoneal, or fallopian tube cancer who developed disease progression after receiving topotecan and/or pegylated liposomal doxorubicin. METHODS Patients were randomized to receive intravenous aflibercept at a dose of either 2 mg/kg or 4 mg/kg every 2 weeks until they developed disease progression or significant toxicity. The primary endpoint was to evaluate Response Evaluation Criteria in Solid Tumor response rates (overall response rate [ORR] = complete responses plus partial responses) and to test the null hypothesis (ORR, >5%). Secondary endpoints included time to tumor progression, safety, progression‐free survival/overall survival, drug pharmacokinetics, and immunogenicity. In total, 67 evaluable patients per cohort were planned based on a Simon 2‐stage design, and, if those patients responded, then enrollment could extend to 200 patients. Tumor radiographic response was assessed by investigators and by an independent review committee. RESULTS After the first 84 evaluable patients, 8 unconfirmed partial responders were noted (ORR, 10%) across both arms; the Independent Data Monitoring Committee recommended continuing blinded accrual. At study completion, 215 evaluable patients were accrued, including 1 responder of 106 patients (0.9%) in the 2‐mg/kg cohort and 5 responders of 109 patients (4.6%) in the 4‐mg/kg cohort according to the independent review committee. The clinical benefit rate (ORR plus stable disease >6 months) was 12.3% and 11% in the 2‐mg/kg and 4‐mg/kg cohorts, respectively. Treatment‐related grade 3 and 4 adverse events included hypertension (25.5% and 27.5% in the 2‐mg/kg and 4‐mg/kg cohorts, respectively), proteinuria (9.4% and 7.3%, respectively), and fatigue (5.7% and 3.7%, respectively). The gastrointestinal perforation rate was low (3 patients; 1.4%). CONCLUSIONS Aflibercept at a dose of either 2 mg/kg or 4 mg/kg was generally well tolerated but did not meet the primary endpoint for response. Cancer 2014;120:335–343. © 2013 American Cancer Society.